PHRASE THEORY: PHRASE TYPES AND SUBTYPES: COORDINATE, SUBORDINATE AND PREDICATIVE PHRASES (FAN, TA’LIM, TEXNOLOGIYA VA ISHLAB CHIQARISH INTEGRATSIYASI ASOSIDA RIVOJLANISH ISTIQBOLLARI, 2024)
This article provides a comprehensive overview of phrase theory, focusing on three specific subtypes: coordinate, subordinate, and predicative phrases. It begins by defining phrases and categorizing them by their heads, such as noun phrases, verb phrases, and prepositional phrases. The discussion then transitions to the subtypes, explaining their roles and offering examples to illustrate their functions within sentences. Coordinate phrases are presented as structures where elements of equal importance are linked by coordinating conjunctions, emphasizing parallelism and balance. Subordinate phrases are described as dependent modifiers or complements that enhance or refine the meaning of a main phrase, introducing additional detail or context.